Summary for the CCAFS Flagship 4 Projects Kick-off Meeting 28-29 January 2014: Result-based Management Trial - Schuetz, Tonya; Cramer, Laura K.; Förch, Wiebke; Jost, Christine; Álvarez, S.; Thornton, Philip K.; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
In order to prepare the transition towards Phase 2, Theme 4 has been identified to spearhead the flagship development process. Flagship 4 (FS4) on Policies and Institutions for Climate-Resilient Food Systems is being phased in from 2014 onwards.